Assessment of biodiversity risks in urban agriculture: Case of Jakarta, Indonesia - Fetty Dwi Rahmayanti; Andi Gunawan; Anas Miftah Fauzi; Edi Santosa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Urban agriculture is a permanent and dynamic part of urban socio-economic and ecological systems. It uses typical urban resources, competes with other urban functions for land and water, is influenced by urban policies and plans, and contributes to urban social and economic development. To assess agricultural sustainability and predict future food security, it is essential to understand the relationship between farming systems and biodiversity. The research aimed to assess biodiversity risk in urban agriculture. This research employed a mixed-methods approach, combining quantitative and qualitative methods, and incorporated a field survey that involved collecting data from research and literature reviews. The field survey involved collecting data from research questionnaires distributed to respondents to determine their perceptions of biodiversity risks to flora and fauna resulting from urban agricultural activities. The results of the study showed that the p-value was greater than the alpha level (α = 0.05), indicating that urban agriculture in East Jakarta does not significantly affect biodiversity risks of flora and fauna. Keywords: agripolitan; city greenery; conservation; East Jakarta; food security